“One Ring to Bind Them All”—Part I: The Efficiency of the Macrocyclic Scaffold for G-Quadruplex DNA Recognition - David Monchaud; Anton Granzhan; Nicolas Saettel; Aurore Guédin; Jean-Louis Mergny; Marie-Paule Teulade-Fichou (Journal of Nucleic Acids)
Macrocyclic scaffolds are particularly attractive for designing selective G-quadruplex ligands essentially because, on one hand, they show a poor affinity for the “standard” B-DNA conformation and, on the other hand, they fit nicely with the external G-quartets of quadruplexes. Stimulated by the pioneering studies on the cationic porphyrin TMPyP4 and the natural product telomestatin, follow-up studies have developed, rapidly leading to a large diversity of macrocyclic structures with remarkable-quadruplex binding properties and biological activities. In this review we summarize the current state of the art in detailing the three main categories of quadruplex-binding macrocycles described so far (telomestatin-like polyheteroarenes, porphyrins and derivatives, polyammonium cyclophanes), and in addressing both synthetic issues and biological aspects.